2018
DOI: 10.1038/s41467-018-03024-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic network biomarker indicates pulmonary metastasis at the tipping point of hepatocellular carcinoma

Abstract: Developing predictive biomarkers that can detect the tipping point before metastasis of hepatocellular carcinoma (HCC), is critical to prevent further irreversible deterioration. To discover such early-warning signals or biomarkers of pulmonary metastasis in HCC, we analyse time-series gene expression data in spontaneous pulmonary metastasis mice HCCLM3-RFP model with our dynamic network biomarker (DNB) method, and identify CALML3 as a core DNB member. All experimental results of gain-of-function and loss-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
166
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 55 publications
1
166
1
2
Order By: Relevance
“…Many studies have revealed that metastasis and recurrence are the most important reasons for the death of patients with HCC . Therefore, we examined the function of NCAPH in migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed that metastasis and recurrence are the most important reasons for the death of patients with HCC . Therefore, we examined the function of NCAPH in migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that metastasis and recurrence are the most important reasons for the death of patients with HCC. 18,19 Therefore, we examined the function of NCAPH in migration and invasion. The results demonstrated that NCAPH could promote the ability of HCC cells to migrate and invade in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have revealed that solid subtype LUAD is more likely to harbor KRAS and TP53 mutations but less likely to harbor EGFR mutations compared to the nonsolid subtypes . However, there is still a lack of effective therapeutic agents targeting KRAS because the blockage of key KRAS effectors may lead to the activation of compensatory or parallel pathways . In order to discover more druggable mutated genes, we identified 356 significantly differentially mutated genes in the TCGA cohort and 639 in the BI cohort.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, there is still a lack of effective therapeutic agents targeting KRAS because the blockage of key KRAS effectors may lead to the activation of compensatory or parallel pathways. 28 In order to discover more druggable mutated genes, we identified 356 significantly differentially mutated genes in the TCGA cohort and 639 in the BI cohort. Only 38 genes overlapped in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Gene regulatory network is turned by temporal transcription with noise. By modelling dynamic network properties (or correlated gene-oscillation) along with disease states (grouped phenotypes), our group and others have identified transcriptomic signals for critical state transitions (Chen, Liu et al, 2012, Mojtahedi, Skupin et al, 2016, Yang, Li et al, 2018. Some of these signals showed clinical significances, for instance epithelial-mesenchymal transition in cancer progression (Jolly, Ware et al, 2017, Tian, Zhou et al, 2018, metabolic transition between tumor and microenvironment (Kianercy, Veltri et al, 2014), and tumor-immune interaction (Lesterhuis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%